Frequent Complications In Chronic Hematogenous Osteomyelitis In Children - Musoyev Sodiqjon Toyirovich (Journal of Science in Medicine and Life, 2024)
Osteomyelitis is an inflammation of the bone marrow, which usually affects all elements of the bone (periosteum, spongy and compact substance). Depending on the etiology of osteomyelitis, it is divided into nonspecific and specific (tuberculosis, syphilitic, brucellosis, etc.); post-traumatic, hematogenous, postoperative, contact. The clinical presentation depends on the type of osteomyelitis and its form (acute or chronic). The basis of treatment of acute osteomyelitis is the opening and sanitation of all wounds, for chronic osteomyelitis - removal and sequestration of cavities, fistulas.